Le collectif d'enseignants, objet de représentations professionnelles : proposition d'un cadre de lecture - Christian Germier (Université de Provence, 2014)
This paper deals with the teachers' professional representations of collectives, while making their own the prescribed text about the device of personal support in the agricultural colleges. The collective work of taking charge of prescribed texts can be taken on by informal collectives of voluntary teachers. The representations of these collectives take their mode of construction (informal versus structured) into account and also their function (emancipating versus protecting). They interact with the representations of the device, of teaching, of the school the teachers work in. This contribution leans on the results of a questionnaire (N=267) and on individual interviews. A framework to read the representations of collectives has been built while analyzing data; it is proposed here and put to the test.